(untitled) (Research, Society and Development, 2022)
Objective: to discuss development experiences and impressions about the use of video games for teaching and learning of nursing students at a University. Method: this is an experience report, developed during the course of parasitology at a University during the second semester of 2020.2, elaborated in three stages: the creation of the game, the previous evaluation by academic volunteers of nursing and biology of the instrument with error identification and application of the educational tool via Google Meet®. Results and discussion: the game underwent adjustments based on the considerations of nursing staff and academics. Final considerations: it appears that the game offered in video format implies a greater engagement of academics in the class, making the teaching-learning process more effective due to the establishment of previously seen knowledge and the opportunity to remove doubts about the issues In addition, it provides opportunities for greater interaction between academics and professors, assessment of student performance in a relaxed environment and student self-assessment.